The Effect of Growth, Leverage, and Profitability on Firm Value with Stock Performance as an Intervening Variable in Property and Real Estate Companies Listed on the IDX - Satoto, Eko Budi (Jurnal Samudra Ekonomi dan Bisnis, 2024)
This study examines how growth, leverage, and profitability influence firm value using stock performance as an intervening variable in property and real estate companies on the IDX. Employing structural equation modeling (SEM) and purposive sampling, the research focuses on 16 companies. Results show a profitable impact on dividends, while leverage has a non-significant negative effect. Dividend policy mediates profitability's influence on firm value. Stock performance is introduced as an intervening variable, offering insights into profitability, leverage, and growth's impact on firm value in the real estate sector. The study advises investors to choose high-profit, low-leverage, high-value companies. Limitations include its sole focus on IDX-listed property and real estate firms.